The Influence of Use Artery-Femoral Band (ARFEBAND) to Haematom Incident in Patients After Percutaneus Coronary Intervention (PCI) - Junait, Junait; Purnomo, Hery Djagat; Ropyanto, Chandra Bagus (IJNP (Indonesian Journal of Nursing Practices), 2018)
AbstractBackground: Haematoma is the main vascular complication in the patients after percutaneous coronary intervention (PCI). This incidents is important to be prevented and be overcome because the internal bleeding is not easy to be control and it can be make extend the mass of patients to inpatient in the hospital. Artery-femoral Band (arfeband) is a device designed that worthy and safe to keep the stability of haemostasis after PCI. Aim: it is to know the influence of use arfeband to haematoma incidents in patients after PCI. Methods: this research used the quasy - experiment pre-post control trial design, it involves 121 patients after the elective of PCI that receives the intervention group (IG) and control group (CG) that is done for 6 hours after the removal of the sheath femoral artery, 60 IG used arfeband and 61 CG with the sand bag. The measurement of diameter haematoma is done when before and after intervention. Results: this research shows that before the intervention, there are no differences that significant between IG and CG p=0,909. There are the significant differences to haem atom incidents after the use of IG with P0,05, OR 0,398 with CI 95%  0,172 – 0,919. It means that arfeband is reducing the haematoma incidents for 60,2 %. The size of the diameter of pre and post procedure, it is decrease in average of 30,4(±13,6)mm to be 10,9 (±15,9) p0,05. Conclusion: The intervention of use arfeband influences to decrease the haematoma incidents significantly after percutaneous coronary intervention (PCI).